HYPERURICEMIA AND THE RELATIONS BETWEEN BLOOD URIC ACID CONCENTRATION, RANDOM BLOOD GLUCOSE AND BMI AMONG ETHNIC POPULATION IN NORTH HALMAHERA - Fiktor Imanuel Boleu; Jubhar C. Mangimbulude; Ferry F. Karwur (Faculty of Public Health, Sriwijaya University, 2018)
Background: Studies of hyperuricemia in societies with a particular ethnic background in Indonesia are interestingly studied because they are related to a number of metabolic indicators/diseases but also because of the unique cultural and genetic contribution that may be significant. This study aims to determine the prevalence of hyperuricemia and it is relationship with other metabolic indicators, especially random blood glucose levels (RBS) and body mass index (BMI) among native ethnic communities in North Halmahera. Methods: A total of 240 respondents from 4 native ethnic communities in North Halmahera were included in the study. Determination of respondents (ethnic origin) was through random selection. Respondent's search was done by identifying the clans representing the family names in each of the ethnic groups in North Halmahera. Data were analyzed using Mann Whitney and Spearman correlation statistics. Results: The prevalence of hyperuricemia is considered high, which is 60% (50,83% male and 69,17% female). Conversely, the prevalence of hyperglycemia is lower with the amount 1,25% (1,67% male and 0,83% female). The prevalence of overweight and obese is respectively 29,17% and 12,50%; with male 30% and 11,67%; and, female 28,33% and 13,33%. There was a positive but not significant correlation between uric acid levels and GDS (r=0.082, ρ=0.207), and there was no significant negative correlation between uric acid levels and BMI in ethnic populations (r=-0.047, ρ=0.468). The relationship between random blood glucose and BMI in all ethnic data showed a positive and significant (r=0.176, ρ=0.006). Conclusions: The prevalence of hyperuricemia (and overweight) among ethnic groups in North Halmahera is very high. Statistically, there is no relationship between levels of RBS and uric acid, as well as the uric acid levels and BMI value in the native ethnic population in North Halmahera. There is a significant positive correlation between the BMI value and the RBS levels.